A long-term experimental study of the reactivity of basement rock with highly alkaline cement waters: Reactions over the first 15 months. (1st October 2016) - Rochelle, C. A.; Milodowski, A. E.; Bateman, K.; Moyce, E. B. A.; Kilpatrick, A.
A series of long-term laboratory experiments was started in 1995 to investigate longer-term dissolution/ precipitation reactions that may occur in the alkaline disturbed zone surrounding a cementitious repository for radioactive waste. They consist of samples of UK basement rock reacting with either Na-K-Ca-OH water ('young' cement porewater) or Ca-OH water ('evolved' cement porewater) at 70°C. This paper summarizes results of reactions occurring over the first 15 months. Experiments of both fluid types showed many similar features, though primary mineral dissolution and secondary mineral precipitation were more extensive in the experiments involving Na-K-Ca (younger) cement porefluids compared to more evolved (Ca-rich) cement porefluids. Dissolution of dolomite, and to a lesser extent silicates (probably K-feldspar, but also possibly mica) occurred relatively rapidly at 70°C. Dolomite dissolution may have been a key factor in reducing pH values, and may be a key mineral in controlling the extent of alkaline disturbed zones. Dissolution was followed by precipitation of brucite close to dolomite grains, at least two generations of C-S-H phases (which may have contained variable amounts of K, Al and Mg); overgrowths of calcite; small crystals of hydroxyapophyllite; and elongate crystals of celestite. Though hydroxyapophyllite was observed (a phase commonly associated with zeolites), there was no evidence for the formation of zeolites in the experiments. Fluid chemical changes track the mineralogical changes, with C-S-H phases being a major control on fluid chemistry. In the 'young' porewater experiments there were decreases in pH, and K, Ca and Mg concentrations, together with transitory increases in SiO2 concentrations. In the 'evolved' porewater experiments there were decreases in pH, Mg, Ca and Sr concentrations, together with small increases in K and SiO2 concentrations. A number of experiments are still running, and will be sampled in coming years.